2003
DOI: 10.1016/s0026-0495(03)00063-5
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -regulatory muscle proteins in the alcohol-fed rat

Abstract: Alcoholic myopathy is characterized by muscle weakness and difficulties in gait and locomotion. It is one of the most prevalent skeletal muscle disorders in the Western hemisphere, affecting between 40% and 60% of all chronic alcohol misusers. However, the pathogenic mechanisms are unknown, although recent studies have suggested that membrane defects occur as a consequence of chronic alcohol exposure. It was our hypothesis that alcohol ingestion perturbs membranelocated proteins associated with intracellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
(33 reference statements)
0
7
0
4
Order By: Relevance
“…However, previous reports regarding chronic EtOH effects on sarco(endo)plasmic reticulum Ca 2ϩ -ATPases (SERCA) collectively suggest similar transitory changes. It has been reported that increased skeletal muscle (SERCA1) protein expression and ATPase activity occur after 6 wk of chronic EtOH exposure (38), and this is accompanied by a reported increase in cardiac SERCA2 activity after 10 wk of chronic EtOH exposure (17). Conversely, SERCA2 protein expression has been reported to be unchanged after 7 mo of chronic EtOH exposure (11), and SR Ca 2ϩ binding and uptake have been reported to be inhibited after 3 mo of chronic EtOH exposure (41).…”
Section: Early Effects Of Chronic Etoh Exposure On Cellular Ec Couplingmentioning
confidence: 99%
“…However, previous reports regarding chronic EtOH effects on sarco(endo)plasmic reticulum Ca 2ϩ -ATPases (SERCA) collectively suggest similar transitory changes. It has been reported that increased skeletal muscle (SERCA1) protein expression and ATPase activity occur after 6 wk of chronic EtOH exposure (38), and this is accompanied by a reported increase in cardiac SERCA2 activity after 10 wk of chronic EtOH exposure (17). Conversely, SERCA2 protein expression has been reported to be unchanged after 7 mo of chronic EtOH exposure (11), and SR Ca 2ϩ binding and uptake have been reported to be inhibited after 3 mo of chronic EtOH exposure (41).…”
Section: Early Effects Of Chronic Etoh Exposure On Cellular Ec Couplingmentioning
confidence: 99%
“…According to recommendations from the National Institute of Alcohol Abuse and Alcoholism’s and the National Heart, Lung and Blood Institute’s sponsored workshop on “Alcohol and the Cardiovascular System: Research Challenges and Opportunities”, 2 key conclusions were made: (i) studies were needed to determine genes de‐regulated in order to assess mechanisms and (ii) pharmacogenomics is needed in determining effective treatment (Lucas et al., 2005). These conclusions were drawn from the fact that excessive alcohol intake results in cardiomyopathy in 15 to 35% of alcoholics, which is thought to account for about half of all cases of heart failure in Western countries (Ohlendieck et al., 2003; Preedy et al., 2003). In addition, alcohol abuse, despite being a major health problem, remains poorly researched and understood in relation to gene regulation and the development of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Надмірна активація процесів вільнорадикального перекисного окиснення спричинює каскад негативних біохімічних реакцій і патологічних змін, які лежать в основі багатьох захворювань людини й тварин, зокрема атеросклерозу, ішемічної хвороби серця, діабетичної ангіопатії, нейродегенеративних та аутоімунних захворювань, раку, променевої хвороби, псоріазу, опіків, катаракти й ін. [5,6]. В ізометричних умовах скорочення м'яза аналіз реєстрованого зусилля, що розвивається м'язом при частотно-модульованій стимуляції її нерва, є якісним показником рівня нейро-й мітопатичних патологічних процесів.…”
unclassified